Saúde mental de professores e as implicações no ensino da educação infantil - (:unkn) unknown (Universidade Federal do Pampa, 2021)
The present dissertation had as general objective to analyze the indicators of mental illness of teachers and the perceptions that they have in relation to the implications of this in the teaching of early childhood education in Uruguaiana/RS. Data collection was carried out through a specific questionnaire, applied through an online platform, between the months of April and May 2020, originating two manuscripts. Manuscript 1 aimed to investigate the prevalence of Minor Psychic Disorders (MPD) and associated factors. 123 teachers participated and answered an electronic questionnaire, separated into two sessions. The first contained questions about sociodemographic aspects, weekly workload, sleeping time, education, number of schools in which it operates, among others. Then, the second part was composed by the Self-Report Questionnaire-20 and aimed to assess the presence of MPD. The cutoff point used to establish suspicion of MPD was ≥ 6 positive responses for men and ≥ 8 for women. For data analysis, descriptive statistical procedures were used through measures of mean, standard deviation, absolute and relative frequencies. For the bivariate analysis, the Chi-square test was used. In all analyses, a significance level of 5% (p<0.05) and a 95% confidence interval were considered. It is concluded that the prevalence of cases indicative of MPD is 34.1%, which is considered high among teachers and that there is evidence of an association between this prevalence and some sociodemographic and health variables. Low family income, poor perception of the remuneration received, not getting 8 hours of sleep, not undergoing psychological counseling and taking psychotropic drugs were positively related to the occurrence of mental suffering. In Manuscript 2, the objective was to analyze the perception of these professionals about mental health and its influence on the teaching of early childhood education. 123 teachers participated and answered an electronic questionnaire, which contained, in addition to sociodemographic questions, questions about their understanding of the concept of mental health, which influences their mental state and this impacts on the teaching-learning processes of the students. After performing the analysis of the results, through the content analysis methodology, proposed by Bardin (2011), it was possible to see that the concept of mental health for the majority is related to having quality of life and well-being, balance and emotional aspects of individuals. While 86.2% believe that the state of their mental health can reflect on the teaching of students and that working conditions and interpersonal relationships are factors to be considered and for that, they understand that having symptoms for mentaldisorders and emotional imbalance can have repercussions. In the teaching-learning processes. Thus, through the two manuscripts generated by this study, it was possible to understand the profile of professionals, whether there is the presence of symptoms for MPD among teachers working in the municipal education network and their perceptions related to the theme of mental health and its impacts. It is noteworthy that the present findings are relevant, raise concern and should be considered to promote actions aimed at prevention and health promotion, aiming at the care and support in mental health for teachers, as well as improvements in working conditions, educational activities to strengthen interpersonal relationships and spaces for listening and welcoming by qualified professionals.
Teachers' mental health and implications for early childhood education
Keywords: Saúde Mental; Educação Infantil; Distúrbios psíquicos menores; Ensino aprendizagem; Mental health; Child education; Minor psychic disorders; Teaching learning; CNPQ::CIENCIAS HUMANAS